2019
DOI: 10.1111/bjd.17927
|View full text |Cite
|
Sign up to set email alerts
|

Pilonidal sinus disease: an intergluteal localization of hidradenitis suppurativa/acne inversa: a cross‐sectional study among 2465 patients

Abstract: Summary Background Hidradenitis suppurativa (HS), also referred to as acne inversa, is a debilitating skin disease characterized by inflammatory nodules, chronic abscesses and tunnels (fistulae and sinuses). The association with pilonidal sinus disease (PSD) is frequently reported but not well documented. Objectives To determine the prevalence and characteristics of inflammatory skin lesions located in the intergluteal fold (IGF) of patients with HS. Methods This was an international multicentre retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 25 publications
0
29
0
2
Order By: Relevance
“…Huang and Kirchhof () noted in their study noted that 68.0% (17/25) of their patients with mild‐to‐moderate HS treated on low‐dose isotretinoin (0.45 mg kg –1 day –1 for 6.8 months) showed partial response, and 53.0% (9/17) of them showed complete response, particularly, with those with lower weight, female gender, and those associated with acne. Benhadou et al () found that the prevalence of pilonidal cyst was around 20% in their studied patients with HS. Patients who have history of pilonidal cyst will benefit from isotretinoin (Patel et al, ).…”
Section: Indications Of Low‐dose Isotretinoin In Dermatologymentioning
confidence: 89%
“…Huang and Kirchhof () noted in their study noted that 68.0% (17/25) of their patients with mild‐to‐moderate HS treated on low‐dose isotretinoin (0.45 mg kg –1 day –1 for 6.8 months) showed partial response, and 53.0% (9/17) of them showed complete response, particularly, with those with lower weight, female gender, and those associated with acne. Benhadou et al () found that the prevalence of pilonidal cyst was around 20% in their studied patients with HS. Patients who have history of pilonidal cyst will benefit from isotretinoin (Patel et al, ).…”
Section: Indications Of Low‐dose Isotretinoin In Dermatologymentioning
confidence: 89%
“…Their sonographic characteristics are also similar and accordingly PD might be a variant of localized form of hidradenitis suppurativa. Their histology is somewhat different, although histology finding cannot be always helpful in distinguishing PD from hidradenitis suppurativa [10].…”
Section: Diagnosis and Managementmentioning
confidence: 98%
“…The next stage is comparative histology, lesional inflammatory mediators and prospective clinical studies in order to validate the work of Benhadou et al . Such work should be encouraged not just in PSD, but also in DCS and AC, where the possibility of common inflammatory and mechanistic pathways may lead to increasing nonsurgical treatment options for patients and a better understanding of these debilitating inflammatory dermatoses.…”
mentioning
confidence: 99%
“…In this issue, Benhadou et al . provide the initial epidemiological evidence required to reconsider PSD as within the spectrum of inflammatory dermatoses related to HS.…”
mentioning
confidence: 99%
See 1 more Smart Citation